Methodology of Islamic Economics: Problems and Solutions - Ahsan Shafiq (Türkiye İslam İktisadı Dergisi)
The title, published by famous Britain based publishing house, Routledge, contains works presented at Research Center for Islamic Economics (IKAM’s) 6th Islamic Economics Workshop and has been edited by a senior faculty member from Istanbul University, Necmettin Kizilkaya. The work is comprised of four sections and fourteen chapters, each of which is written by a separate author, all adroit experts of their peculiar fields. Each of the chapters brings to light a separate dimension of the methodology yet all of them are coherently connected and together help elucidate misconceptions related to methodological conundrum in Islamic economics.